Chinese undergraduates' preferences for altruistic traits in mate selection and personal advertisement: Evidence from Q‐sort technique. (3rd September 2015) - Guo, Qingke; Feng, Linlin; Wang, Mingming
Abstract : Human's preferences for altruistic mates have been confirmed by many researchers. Under the deep influence of Confucianism that authorised more parental control over offspring's mate selection, Chinese people's mating strategies and mate preferences may be different from what the evolutionary psychologists have suggested. This study used the Q‐sort technique to assess the roles of altruistic traits in mate selection and personal advertisement. A total of 200 university students participated in the Q‐sort procedures and were asked to sort 50 traits (among which altruistic traits were mixed) according to their importance when choosing (or advertising to) a long‐term (LT) or a short‐term (ST) mate. Our findings were quite different from prior studies. When Chinese participants chose a mate or advertised themselves to a potential mate, kin altruism was considered to be the most important trait; altruistic traits were more preferred by males than by females and females tended to advertise themselves as more altruistic; preferences for altruistic traits showed no difference between LT and ST mate selections (or between personal advertisement to a LT and a ST mate).